CLINICAL OUTCOMES AND PATIENT CHARACTERISTICS ACCORDING TO THE COMBINATION OF TEN-YEAR RISK OF ATHEROSCLEROTIC CARDIOVASCULAR DISEASE AND SYSTOLIC BLOOD PRESSURE. (April 2021) - Harris, Katie; Jun, Min; Oshima, Megumi; Woodward, Mark; Menard, Joel; Chalmers, John
Abstract: Objective: Improving the efficiency of hypertension management has driven treatment indications to be based on cardiovascular disease risk calculations instead of blood pressure or cholesterol management. The aim of this study was to explore the relationship between ten-year risk of atherosclerotic cardiovascular disease (ASCVD) and systolic blood pressure (SBP) in individuals with type 2 diabetes and describe the characteristics of individuals according to their ASCVD risk and SBP cross-classification. The secondary aim was to model the association of ASCVD risk and SBP at study baseline with clinical outcomes (major macrovascular, major microvascular and death). Design and method: This current study used 7, 426 individuals from the Action in Diabetes and Vascular Disease: PreterAx and DiamicroN Modified-Release Controlled Evaluation (ADVANCE) randomised clinical trial, that were free from macrovascular disease at baseline. ASCVD risk and SBP were categorised into approximate thirds, reflecting clinically meaningful cut points, defined as intermediate risk: ASCVD < 20 or SBP < 130, high risk: ASCVD 20 -34 or SBP 130–149, and very high risk: ASCVD > = 35 or SBP > = 150. Individuals were cross-classified according to their ASCVD and SBP categories. Characteristics of individuals among the categories were summarised using descriptive statistics. Cox proportional hazards models were fitted to model the association of ASCVD and SBP cross-classification with clinical outcomes. Results: There was a high proportion of women for ASCVD < 20 across the three sequential SBP categories (67.3%, 80.3% and 87.6%). Mean age increased through increasing ASCVD risk categories, in all risk categories the mean age was highest for SBP < 130 and lowest for SBP > = 150. The risk of death increased as ASCVD increased; though there was no significant association of SBP within the ASCVD categories. The risk of major macrovascular events increased sequentially through the combined effect of ASCVD and SBP (see figure). The highest risk of major microvascular events was for SBP > = 150 across all ASCVD categories. Conclusions: The cross-classification of ASCVD and SBP yielded varying associations with death, major macrovascular and major microvascular events, thus indicating that using ASCVD and /or SBP as predictors produces a non-uniform pattern for adverse clinical outcomes. Figure. No caption available.